Analisis Permasalahan Pertumbuhan Ekonomi di Negara Indonesia - Rauf, Spandi; Latif, Abdul (Jurnal Ilmiah Global Education, 2024)
The economic growth of Indonesia was triggered by commodity export sectors such as oil, gas, and agricultural products at the dawn of independence. However, changes in economic policies in the 1960s propelled the development of the manufacturing and heavy industry sectors. Several main factors supporting Indonesia's economic growth include structural reform policies, investment in infrastructure, and the advancement of the information technology sector. However, challenges such as economic disparities between regions, global uncertainty, and environmental issues also influence the course of economic growth. The impact of significant economic growth is evident in increased per capita income, decreased poverty rates, and improved access to education and healthcare services. Nevertheless, economic growth also brings negative impacts such as economic inequality that requires serious attention. In facing the future, Indonesia needs to maintain a balance between sustainable economic growth and environmental protection. Policies that support economic diversification, investment in human resources, and the development of innovative sectors will be the key to addressing global challenges and ensuring inclusive and sustainable economic growth in Indonesia.